KONSTRUK PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN BERBASIS MASALAH UNTUK MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS PESERTA DIDIK - Kusnadi, Edi; Martini, Eneng; Nugraha, Galih Nurdin (IKIP PGRI PONTIANAK, 2017)
Education should be directed at improving the quality of learning. Improving the quality of teaching is one of the targets to be pursued by every educator in every lesson plans are made. Learning will be successful, if educators concerned about the situation and the conditions in which learning takes place. Based on preliminary observations and the observations made by researchers on learning activities in SMA Conggeang Sumedang, obtained by the fact that that the application of the models of learning in the classroom has not influence on the critical thinking skills of learners, as most teachers still use lecture learning model. One attempt to solve the above problems, namely the problem based learning model that is a model of learning is done by the provision of stimulus in the form of problems and then do problem solving by students who are expected to add skills in critical thinking to understand the learning materials. Application of Problem Based Learning Model in the classroom, the implementation can use multiple methods and media stimulus. The implications of the implementation of Problem Based Learning Model in teaching civics is able to create a familiar suasanan learning among peers (students), democratic in terms of civics referred to as a laboratory of democracy, as well as a communicative and interactive classes.